Measurement of the tt¯ $$ t\overline{t} $$ production cross-section in pp collisions at s $$ \sqrt{s} $$ = 5.02 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Top Physics.; Springer Open.